Number of Hofbauer Cells in Placentae from Normal and Pre Eclamptic Gestation - Ifra Saeed , Ayesha Yousaf , Shaista Ali (Journal of Rawalpindi Medical College, 2018)
Background:. To compare the number of Hofbauer cell in placenta from normal pregnancy with placenta complicated by pre eclampsia Methods: For this comparative study, fifty placentae were taken from normotensive mothers (Normotensive group) and fifty placentae were taken from mothers with hypertension (Hypertensive group). Placentae were fixed in formalin for 48 hours. Placentae were divided into four parts, after fixation and 5mm tissue was taken from the center of randomly selected two parts. After tissue processing and staining, number of Hofbauer cells was counted in both groups. Results: The number of Hofbauer cells was increased in hypertensive group. The quantitative difference between number of Hofbauer cells in normotensive and hypertensive groups were statistically significant. Conclusion: Number of Hofbauer cells was increased in hypertensive group and it may be the result of placental hypoxia which is a common finding in pre eclampsia